Evaluation of dielectric elastomers to develop materials suitable for actuation. Issue 48 (1st December 2021) - Banet, Philippe; Zeggai, Nouh; Chavanne, Jonathan; Nguyen, Giao T. M.; Chikh, Linda; Plesse, Cédric; Almanza, Morgan; Martinez, Thomas; Civet, Yoan; Perriard, Yves; Fichet, Odile
Abstract : Commercial dielectric elastomers and their modification methods are reviewed. A method is proposed to overcome the complex interdependency of their properties allowing quick comparison and selection of suitable materials for soft actuator applications. Abstract : Electroactive polymers based on dielectric elastomers are stretchable and compressible capacitors that can act as transducers between electrical and mechanical energies. Depending on the targeted application, soft actuators, sensors or mechanical-energy harvesters can be developed. Compared with conventional technologies, they present a promising combination of properties such as being soft, silent, light and miniaturizable. Most of the research on dielectric elastomer actuators has focused on obtaining the highest strain, either from technological solutions using commercially available materials or through the development of new materials. It is commonly accepted that a high electrical breakdown field, a low Young's modulus and a high dielectric constant are targets. However, the interdependency of these properties makes the evaluation and comparison of these materials complex. In addition, dielectric elastomers can suffer from electromechanical instability, which amplifies their complexity. The scope of this review is to tackle these difficulties. Thus, first, two physical parameters are introduced, one related to the energy converted by the dielectric elastomer and another to its electromechanical stability. These numbers are then used to compare dielectric elastomers according to a general and rational methodology considering their physicochemical and electromechanical properties. Based on this methodology, different families of commercially available dielectric elastomers are first analyzed. Then, different polymer modification methods are presented, and the resulting modified elastomers are screened. Finally, we conclude on the trends enabling the choice of the most suitable modification procedure to obtain the desired elastomer. From this review work, we would like to contribute to affording a quick identification method, including a graphic representation, to evaluate and develop the dielectric materials that are suitable for a desired actuator.